2023
DOI: 10.18087/cardio.2023.3.n2328
|View full text |Cite
|
Sign up to set email alerts
|

Is the Naples prognostic score useful for predicting heart failure mortality

Abstract: Aim    The Naples prognostic score (NPS) simultaneously evaluates inflammation and malnutrition, which are two main factors that play a role in the pathophysiology and prognosis of heart failure (HF). In this study, we aimed to examine the relationship of NPS with in-hospital mortality of hospitalized patients with a diagnosis of HF.Material and Methods    A total of 496 hospitalized HF patients included in this study. The patients were divided into two groups as deceased and living. The clinical and demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Two recent studies have investigated the relationship between NPS and the prognosis of HF patients. Kilic et al [ 12 ] demonstrated a strong correlation between NPS and mortality in HF. Erdogan et al [ 11 ] showed that NPS was associated with mortality and rehospitalization in patients with decompensated HF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies have investigated the relationship between NPS and the prognosis of HF patients. Kilic et al [ 12 ] demonstrated a strong correlation between NPS and mortality in HF. Erdogan et al [ 11 ] showed that NPS was associated with mortality and rehospitalization in patients with decompensated HF.…”
Section: Discussionmentioning
confidence: 99%
“…This score has recently been associated with worse outcomes in patients with acute coronary syndrome and heart failure (HF). [10][11][12][13] However, the role of the NPS score in PAH has not yet been studied. We aimed to assess the prognostic impact of NPS in patients with PAH.…”
mentioning
confidence: 99%
“…The NPS was first validated as a prognostic factor for patients undergoing colorectal cancer surgery [ 7 , 8 ]. Recent studies have demonstrated that NPS is associated with mortality due to heart failure and short- and long-term outcomes in patients with ST-segment elevation myocardial infarction [ 9 , 10 , 11 , 12 ]. Since the outcomes after TAVR are closely linked to inflammation and nutritional status, we aimed to investigate the correlation between the NPS and prognosis after TAVR with a one-year follow-up in our study.…”
Section: Introductionmentioning
confidence: 99%